Hydrogen sieving from intrinsic defects of benzene-derived single-layer graphene. (November 2019) - Khan, Majharul Haque; Moradi, Mina; Dakhchoune, Mostapha; Rezaei, Mojtaba; Huang, Shiqi; Zhao, Jing; Agrawal, Kumar Varoon
Abstract: Single-layer graphene films, crystallized by chemical vapor deposition, host a low density of vacancy defects that are attractive for the size-sieving of molecules. The size and the density of such defects are a function of the growth temperature and the carbon precursor. So far, the studies applying the intrinsic defects of graphene have only used CH4 as the precursor. Since there are reports claiming the synthesis of graphene from benzene at low temperature (up to 100 °C on Cu foil), we systematically studied the crystallization of benzene-derived graphene and the evolution of intrinsic defects. We demonstrate that graphene cannot grow from benzene below 700 °C on Cu. We attribute the reports on low-temperature growth of graphene to the practice of pre-annealing of the Cu foil at 1000 °C and to the unintentional benzene residues in the reactor if the reactor is not purged carefully. Finally, we report that high-quality single-layer-graphene can be synthesized using benzene above 825 °C. The majority of vacancy defects in benzene-derived graphene (900–1000 °C) are smaller than 0.38 nm, leading to an attractive H2 sieving (H2 permeance over 2000 gas permeation units; H2 /C3 H8 and H2 /SF6 selectivities of 12 and 50, respectively). Graphical abstract: Image 1